ANALYSIS OF LOVE OF MONEY WITH THE PERCEPTION OF ACCOUNTING STUDENTS ETHICS - Dea Maudya Rachmah; Asep Kurniawan (JASS (Journal of Accounting for Sustainable Society), 2019)
The purpose of the study is to find out whether the love of money affects the ethical perception of accounting students. The survey was developed based on the Kecurang action and the love of the money scale given to 57 undergraduate accounting students in two colleges.-The approach used is multiple linear regression, based on test T and test F for the processing of data performed. Student accounting looks at fraudulent actions outside of class because it is more unethical than a cheating in the classroom. Because outside of class will cause unwanted factors by money lovers.